A novel rat model of interbody fusion based on anterior lumbar corpectomy and fusion (ALCF) - Yu Kang (BMC, 2021)
Abstract Background Rats have been widely used as experimental animals when performing fundamental research because they are economical, rapidly reproducing, and heal quickly. While the rat interbody fusion model has been applied in basic studies, existing rat models generally have shortcomings, such as insufficiently simulating clinical surgery. The purpose of this study was to develop a novel rat model of interbody fusion which more closely represents clinical surgery. Methods The internal fixation was designed based on physical measurements of the rats’ lumbar spine. Then, ten rats divided into two groups (A and B) underwent anterior lumbar corpectomy and fusion of the L5 vertebrae. Groups A and B were sacrificed four and 8 weeks post-surgery, respectively. Micro-CT and histological examination were used to evaluate the model. Fusion rate, bone volume fraction (BV/TV), trabecular bone number (Tb.N), trabecular bone thickness (Tb.Th), and the area ratio of newly formed bone (NB) were calculated for quantitative analysis. Results Based on the L5 body dimensions of individual rats, 3D-printed titanium cage of the appropriate size were printed. The operations were successfully completed in all ten rats, and X-ray confirmed that internal fixation was good without migration. Micro-CT suggested that fusion rates in group B (100%) were greater than group A (40%, P < 0.05). The BV/TV (B: 42.20 ± 10.50 vs. A: 29.02 ± 3.25, P < 0.05) and Tb.N (B: 4.66 ± 1.23 vs. A: 1.97 ± 0.40, P < 0.05) were greater in group B than A, and the Tb.Th in group B was lower than group A (B: 0.10 ± 0.04 vs. A: 0.15 ± 0.02, P < 0.05). Histomorphometry results demonstrated that the area ratio of NB in group B were greater than group A (B: 35.72 ± 12.80 vs. A: 12.36 ± 16.93, P < 0.05). Conclusion A rat interbody fusion model based on anterior lumbar corpectomy and fusion has successfully been constructed and verified. It could provide a new choice for fundamental research using animal models of spinal fusion.